Physical–chemical characterization and antioxidant properties of extruded products made from mixtures composed of corn grits and red potato flour (Oxalis tuberosa) - Lizbeth González Victoriano; Norma Guemes Vera; Luis A. Chel Guerrero; Aurea Bernardino Nicanor; Sergio Soto Simental; José J. Chanona Pérez; Aurora Quintero Lira (CyTA - Journal of Food, 2019)
Some physicochemical characteristics and antioxidant activity of extrudates made from corn grits and red potato flour were evaluated. The inclusion of red potato flour altered values of water absorption index, water solubility index, expansion index and fracturability of extrudates. Color analysis of extrudates showed a reduction of luminosity from 44.37 ± 0.87 to 25.06 ± 1.74. Likewise, extrudates made with red potato flour at 100% presented higher content of total phenols compared to the control extrudates (0.44 ± 0.02 and 2.88 ± 0.03 mg GA/g dry sample, respectively); consequently, an increase in antioxidant capacity was observed using DPPH, ABTS and FRAP assays. The images obtained by fluorescence microscopy provided information on the protein content. The proximal chemical analysis indicated that extrudates substituted with red potato flour at 10% showed higher protein content (7.78 g/100 g), compared to T5. This study concludes that when adding red potato flour, is possible to develop extrudates with good physicochemical characteristics and antioxidant properties.